Association of calcium channel blocker use with clinical outcome of COVID-19: A meta-analysis - Mochamad Yusuf Alsagaff, - (Elsevier, 2021)
Aims This meta-analysis aims to analyze the association of calcium channel blocker (CCB) use with COVID-19 clinical outcomes.